Temporal and notational comparison of badminton matches between men's singles and women's singles - Abian-Vicen, J.; Castanedo, A.; Abian, P.; Sampedro, J. (International Journal of Performance Analysis in Sport, 2013)
The purpose of the study was to compare the temporal and notational structures in games and matches between men's singles (MS) and women's singles (WS) in the current top level of world badminton players. Ten matches of each event (n=20), from the official videos of the Beijing 2008 Olympic Games, were analyzed. Match duration (MS: 2378.0±387.9 s, WS: 1696.1±170.4 s.; P<0.05), real time played (MS: 613.7±80.1 s and WS: 493.6±70.2 s; P<0.05), rally time, rest time and shots per rally were significantly higher in men's singles than in women's singles, whereas work density and percentage of time played (MS: 26.0±2.1%, WS: 29.0±2.0%; P<0.05) were higher in women's single. There were no differences in variables between the first and the second game in any event. For the final shot of each rally it was observed that the unforced error, the smash, the net and the drive were the most decisive shots in matches. It was also found differences (P<0.05) between the two events; the smash and the drive were commonly used by men and the drop was commonly used by women. In conclusion the temporal and notational structure of the badminton match was different when comparing men's singles from women's singles.